Teaching ESP to students of accounting major at Hai Duong College of Economics and Technology: problems and solutions - Phan, Thị Hiền (University of Languages and International Studies, 2017)
Part A: Introduction. Part B: Development. ( Chaptet 1: Literature review. Chapter 2: The teaching context. Chapter 3: Research methodology. Chapter 4: Findings and discussion. Chapter 5: Recommendations). Part C: Conclusion